The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s00405-020-06319-7
|View full text |Cite
|
Sign up to set email alerts
|

Otolaryngological symptoms in COVID-19

Abstract: The aim of this study was to evaluate the frequency of various otolaryngological symptoms in patients with COVID-19 with regard to age, gender and pneumonia-related thorax CT characteristics. Methods This is a retrospective study conducted between March 25, 2020 and April 25, 2020. The anamnesis and medical files of 155 patients who applied to our outpatient COVID-19 clinic were evaluated. Patients with positive PCR tests for COVID-19 who were aged between 18-72 years were divided into groups according to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
115
0
13

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(131 citation statements)
references
References 13 publications
3
115
0
13
Order By: Relevance
“…Coronavirus-related otoneurological symptoms, such as tinnitus and balance disorders, have been described so far [ 10 , 23 29 ], as neurotrophic and neuroinvasive capabilities are typical of some coronaviruses [ 30 ]. Previous studies on other coronavirus infections showed a brain involvement, focusing attention on the possible neuro-auditory impairment following this infection [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coronavirus-related otoneurological symptoms, such as tinnitus and balance disorders, have been described so far [ 10 , 23 29 ], as neurotrophic and neuroinvasive capabilities are typical of some coronaviruses [ 30 ]. Previous studies on other coronavirus infections showed a brain involvement, focusing attention on the possible neuro-auditory impairment following this infection [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the growing amount of scientific literature on COVID-19, studies that correlate audiovestibular symptoms to SARS-CoV-2 infection are still limited and further investigation is necessary for a better estimate of their incidence [ 10 , 23 29 ]. Furthermore, the incidence of audiovestibular symptoms among patients infected with other types of coronavirus (i.e., MERS and SARS) is debated [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bell’s palsy related to COVID-19 is uncommon as only 1 of 89 otolaryngologic symptom presenting patients reported Bell’s palsy [ 152 ]. Case studies have primarily reported the relationship between Bell’s Palsy and COVID-19.…”
Section: Sars-cov-2 Infection Of the Nervous Systemmentioning
confidence: 99%
“…Proposed mechanisms include direct viral invasion, reactivation of a latent virus within the spiral ganglion, and an immune-mediated mechanism in a systemic viral infection [ 5 ]. Currently, the damaging impact of COVID-19 virus on the hearing organs in the inner ear is a new finding yet to be explored [ 6 , 7 , 8 ]. Otitis has already been highlighted as an unusual presentation of COVID-19, in conjunction with usual viral symptoms or as an isolated disorder [ 8 , 9 , 10 , 11 , 12 ].…”
mentioning
confidence: 99%